Marifat Marjani Sebagai Salah Seorang Pendiri Provinsi Riau (Jurnal Ilmu-Ilmu Sejarah, Budaya Dan Sosial ( LENTERA ), 2009)
The purpose of this research is to observe the struggle of Marifat Marjani which is the only one of Riau people who sat at Parliament fromPaerti Part) by not forgeting other personages struggle. The result of thisstruggle was Undang-Undang Darurat No. 19/ 1957 about formation ofterritory Suatantra in West Sumatra, Jambi, Riau by central governmentwhich the first governor was Mr. S. M Amin and the capital city was inTanjung Pinang.Keyword : Founder, Perti